A durable MXene-based zinc ion hybrid supercapacitor with sulfated polysaccharide reinforced hydrogel/electrolyte. Issue 42 (21st October 2021) - Cui, Haonan; Mi, Hongyu; Ji, Chenchen; Guo, Fengjiao; Chen, Yanna; Wu, Dandan; Qiu, Jieshan; Xie, Haijiao
Abstract : A N-doped MXene wrapped with N-doped amorphous carbon was synthesized. DFT results reveal an enlarged work function of N-Ti3 C2 (OH)2 @N–C. A durable MXene-based ZHSC with reinforced PAM- co -PAA/κ-CG/ZnSO4 hydrogel demonstrates excellent electrochemical performance. Abstract : Zn-ion hybrid supercapacitors (ZHSCs) have emerged as promising equipment for energy storage applications due to their eco-efficiency, abundant natural resources, and high safety. However, the development of ZHSCs remains at the initial stage and substantial efforts regarding electrode materials and hydrogel/electrolytes are still needed for further enhancing the charge storage ability. Herein, a crumpled nitrogen-doped MXene wrapped with nitrogen-doped amorphous carbon (denoted as NMXC) was synthesized through a template-guided route for modulating the surface chemistry and expanding the inter-lamellar spacing of the MXene. Density functional theory (DFT) calculation revealed that the N-doping effect enhances the electronic conductivity of MXene and the MXene heterostructure with an N-doped carbon layer possesses an enlarged work function as compared with the pure MXene, which effectively prevents the electrochemical oxidation and enables stable operation at higher positive potential. For these reasons, NMXC exhibits a higher capacity and wider operating voltage window as compared with pure MXene, and better rate performance than melamine formaldehyde-derived N-doped carbon (NC). A dual crosslinked hybrid polymeric hydrogel/electrolyte (denoted as PAM- co -PAA/κ-CG/ZnSO4 ) was also designed, which was obtained by forming intermolecular hydrogen bonds between ionic κ-carrageenan (denoted as κ-CG) double helix chains and the covalent poly(acrylic amide-acrylic acid) (denoted as PAM- co -PAA) main matrix. The test results show that the PAM- co -PAA/κ-CG/ZnSO4 hydrogel/electrolyte possesses a higher ionic conductivity of 1.76 S m −1, higher stretchability of 626.0%, and satisfactory compressibility. In addition, the quasi-solid-state ZHSC based on the NMXC cathode and PAM- co -PAA/κ-CG/ZnSO4 hydrogel/electrolyte demonstrated a low self-discharge rate of 1.75 mV h −1, a high capacity with 96.4% capacity retention after 10 000 cycles along with high energy/power densities of 54.9 W h kg −1 /3314.4 W kg −1 .